IL-17 inhibits chondrogenic differentiation of human mesenchymal stem cells. - Masahiro Kondo (PLoS ONE, 2013)
OBJECTIVE: Mesenchymal stem cells (MSCs) can differentiate into cells of mesenchymal lineages, such as osteoblasts and chondrocytes. Here we investigated the effects of IL-17, a key cytokine in chronic inflammation, on chondrogenic differentiation of human MSCs. METHODS: Human bone marrow MSCs were pellet cultured in chondrogenic induction medium containing TGF-β3. Chondrogenic differentiation was detected by cartilage matrix accumulation and chondrogenic marker gene expression. RESULTS: Over-expression of cartilage matrix and chondrogenic marker genes was noted in chondrogenic cultures, but was inhibited by IL-17 in a dose-dependent manner. Expression and phosphorylation of SOX9, the master transcription factor for chondrogenesis, were induced within 2 days and phosphorylated SOX9 was stably maintained until day 21. IL-17 did not alter total SOX9 expression, but significantly suppressed SOX9 phosphorylation in a dose-dependent manner. At day 7, IL-17 also suppressed the activity of cAMP-dependent protein kinase A (PKA), which is known to phosphorylate SOX9. H89, a selective PKA inhibitor, also suppressed SOX9 phosphorylation, expression of chondrogenic markers and cartilage matrix, and also decreased chondrogenesis. CONCLUSIONS: IL-17 inhibited chondrogenesis of human MSCs through the suppression of PKA activity and SOX9 phosphorylation. These results suggest that chondrogenic differentiation of MSCs can be inhibited by a mechanism triggered by IL-17 under chronic inflammation.